2014
DOI: 10.1016/j.jtusci.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Method development and validation for simulataneous estimation of albendazole and praziquantel in bulk and in a synthetic mixture

Abstract: A simple, rapid, sensitive reversed-phase high-performance liquid chromatography method was developed and validated for simultaneous measurement of albendazole and praziquantel with an internal standard, simvastatin, at single wavelength of 225 nm. Chromatographic separation was performed on an Enable C 18 column (250 mm × 4.6 mm, 5 m: Spinco Biotech Pvt Ltd) and a mobile phase consisting of acetonitrile:water (60:40, v/v) with 10% orthophosphoric acid to adjust the pH to 3.2, at a flow rate of 1.0 ml/min. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…In this study calibration graphs containing in the range of 0.05 to 10 ugml-1 of ABZ, ABZSO and ABZSO2 with calibration curves were linear (r2 ≥ 0.990) which is similarly reported by (Shah et al, 2014;Shaikh et al, 2003). A 20 mg single dosage was given through oral intubation, intramuscular and intraperitoneal, the drug was found in oral dose only.…”
Section: Concentration Of Abz Abzso and Abzso 2 In Plasmasupporting
confidence: 82%
“…In this study calibration graphs containing in the range of 0.05 to 10 ugml-1 of ABZ, ABZSO and ABZSO2 with calibration curves were linear (r2 ≥ 0.990) which is similarly reported by (Shah et al, 2014;Shaikh et al, 2003). A 20 mg single dosage was given through oral intubation, intramuscular and intraperitoneal, the drug was found in oral dose only.…”
Section: Concentration Of Abz Abzso and Abzso 2 In Plasmasupporting
confidence: 82%
“…Linearity is the ability to elicit results through the analysis of diverse concentrations within a given range (Shabir, 2003;Shah et al, 2014). A linear regression analysis (n = 3) was measured over seven different concentrations (12.5-400 μg/mL), and its regression equations are given in Table 2.…”
Section: Validation Of the Proposed Analytical Methodsmentioning
confidence: 99%
“…1,2 An extended literature survey revealed that few analytical methods [using high-performance liquid chromatography (HPLC) and HPLC-mass spectrometry] have been reported for estimation of praziquantel. [3][4][5][6][7] To date, one spectrofluorimetric method has been reported for praziquantel quantification in blood plasma and urine. However, the method was complicated because of drug chemical derivatization with dansyl chloride, which involved various solvents with many extraction procedures.…”
Section: Introductionmentioning
confidence: 99%